Evaluation of Concrete with Partial Replacement of Cement by Waste Marble Powder - Mushraf Majeed; Anwar Khitab; Waqas Anwar; Raja Bilal Nasar Khan; Affan Jalil; Zeesshan Tariq (Civil Engineering Journal, 2021)
This study aims to evaluate concrete having Waste Marble Powder (WMP) as partial replacement of cement. Marble is the metamorphic form of limestone (CaCO3) and WMP was chosen as substitute of cement on account of its high calcium oxide content. WMP is by-product of marble industry and is an environmental burden. The manufacturing of cement is also environmentally hazardous owing to emission of greenhouse gases. Thus, the recycling of WMP in place of cement in concrete offers two ecological advantages. Thirdly, WMP has a specific gravity of 2.6 against that of 3.15 for cement, which reduces the weight of the finished products. Based on the previous studies, five different concrete mixes were prepared having 0, 5, 10, 15 and 15% replacement levels. The samples were evaluated both through destructive and non-destructive tests.  Destructive tests included compressive, tensile and flexural strengths, whereas non-destructive tests comprised of ultrasonic pulse velocity (UPV) and rebound hammer. It was observed that the workability decreases with WMP inclusion owing to its higher water absorption, which inhibits lubrication of cement particles. The concrete strength improves up to a replacement level of 10% by mass of cement on account of densification created by the finer WMP and un-hydrated cement particles, which act as hard inclusions. Beyond 10%, the concrete strength starts declining due to insufficient quantity of cement matrix, binding the WMP particles. Schmidt rebound numbers authenticate the compressive strength results: The number increases up to 10% replacement level and beyond 10% it decreases. The results of UPV indicate that the velocity increases with increase in WMP content: The increase is attributed to compactness of the composite with finer WMP particles. Doi: 10.28991/cej-2021-03091637 Full Text: PDF